2006
DOI: 10.1007/s12055-006-0559-z
|View full text |Cite
|
Sign up to set email alerts
|

D-transposition of great vessels with intact ventricular septum presenting at 3–8 weeks: Should all go for rapid two stage arterial switch or primary arterial switch

Abstract: Background: Fontan procedure and its modifications are established procedures for the treatment of anatomical defects with a single ventricle physiology.Methods: Thirty-two patients underwent extra-cardiac Fontan procedure between Feb 2004 and Oct 2005. Pre-operative cardiac catheterization was done in all patients. All cases were operated on cardiopulmonary bypass with beating heart. ePTFE conduit (Gore-Tex) was used to create an extra cardiac connection between inferior vena cava and the pulmonary artery. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…In children presenting up to 6 weeks, we found primary ASO to be a better surgical option than rapid two-stage ASO [8]. Similar studies from other centres show encouraging results of primary ASO in children more than 3 weeks of age [1].…”
Section: Introductionsupporting
confidence: 71%
See 2 more Smart Citations
“…In children presenting up to 6 weeks, we found primary ASO to be a better surgical option than rapid two-stage ASO [8]. Similar studies from other centres show encouraging results of primary ASO in children more than 3 weeks of age [1].…”
Section: Introductionsupporting
confidence: 71%
“…Conventionally, these children are offered atrial level switch, which has been proved to be an inferior operation as compared to arterial switch [2,3]. Another option is to carry out ventricular training and then switch the arteries, which has evolved over a period of time from being a two-stage to a rapid two-stage operation; but our earlier study revealed primary arterial switch to be a better alternative [8]. Published literature has already established the ASO to be far better than atrial switch in physical functioning, mental health, self-esteem and general health perception.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the following years, late ASO performance was reported at an increasing rate. [11] Furthermore, a study comparing the results of infants older than three weeks who underwent two-stage ASO and primary ASO suggested that the results were in favor of primary ASO. [11] In the literature review, it can be concluded that late ASO can be performed successfully in the older months and even at around the age of eight.…”
Section: Discussionmentioning
confidence: 99%
“…[11] Furthermore, a study comparing the results of infants older than three weeks who underwent two-stage ASO and primary ASO suggested that the results were in favor of primary ASO. [11] In the literature review, it can be concluded that late ASO can be performed successfully in the older months and even at around the age of eight. [4] On the other hand, it was reported that performing primary ASO with ECMO support was a safe and appropriate approach to ensure postoperative LV support in infants aged above 21 days.…”
Section: Discussionmentioning
confidence: 99%